Hirschsprung Disease in Adults: A Case Report in a Tertiary Hospital in West Africa - Sogan, Ananivi; Amouzou, Efoe-Ga; Sesime Sanni, Yawa; Sabi, Hassiatou; Adjenou, Victor; James, Komlanvi (European Scientific Journal, ESJ, 2022)
Hirschsprung disease in adults is a rare and frequently misdiagnosed cause of long-standing and refractory constipation. Surgical procedures initially developed for pediatric patients are applied to adults with varying degrees of success. A nineteen-year-old girl was diagnosed with Hirschsprung disease in a tertiary hospital of low technology level in Togo. Soave-Boley’s procedure was used as definitive surgical management which resulted in a good outcome.